Immunohistochemical study of thrombospondin and its receptors alpha root of beta 3 and CD36 in normal thyroid and in thyroid tumours. Issue 12 (1st December 1999) - Patey, M; Delemer, B; Bellon, G; Martiny, L; Pluot, M; Haye, B
Abstract : AIM: To describe the pattern of distribution of thrombospondin (TSP1) and its receptors, alpha root of beta 3 integrin and CD36, in normal human thyroid tissue and to compare their expression in different benign and malignant thyroid conditions. METHODS: Immunohistochemistry was used to study TSP1 and its receptors in 40 surgical thyroidectomy specimens (normal parenchyma, 7; follicular adenoma, 4; multinodular goitre, 13; papillary carcinoma, 6; follicular carcinoma, 8; anaplastic carcinoma, 2). RESULTS: In the normal thyroid parenchyma, there was weak expression of TSP1 limited to the vessels with no staining of the extracellular matrix. In goitres, the expression of TSP1 was more pronounced in areas of fibrosis, with staining of alpha root of beta 3 on thyrocytes located in the vicinity. In thyroid adenomas, expression of TSP1 was slightly enhanced compared with normal tissue, located in the basement membrane of vessels. In papillary carcinomas, TSP1 was abundant in the desmoplastic stroma with a cytoplasmic distribution of alpha root of beta 3 integrin in thyrocytes. In follicular carcinomas, TSP1 was less abundant in the extracellular matrix, limited to the vessels of the stroma with a weaker expression of alpha root of beta 3 on thyrocytes than in papillary carcinomas. In anaplastic carcinomas, TSP1 was only present in the numerous capillaries of the stroma, with a marked positivity for alpha root of beta 3 in one case. No immunostaining of thyrocytes is observed with CD36. CONCLUSIONS: These results suggest the importance of the interaction between alpha root of beta 3 integrin and TSP1 during remodelling of the matrix in fibrous goitres with areas of early sclerosis comparable with wound healing. In papillary carcinomas, the overexpression of TSP1 restricted to the stroma suggests protective effects against tumour progression.